Subcutaneous Adipose Tissue from Obese and Lean Adults Does Not Release Hepcidin In Vivo - Lisa Tussing-Humphreys; Keith N. Frayn; Steven R. Smith; Mark Westerman; A. Louise Dennis; Elizabeta Nemeth; Jessica Thomson; Cenk Pusatcioglu (The Scientific World Journal)
Hepcidin is the main regulator of systemic iron homeostasis and is primarily produced by the liver but is also expressed, at the mRNA-level, in periphery tissues including the subcutaneous and visceral adipose tissue. Obesity is associated with elevated hepcidin concentrations and iron depletion suggesting that the exaggerated fat mass in obesity could contribute significantly to circulating hepcidin levels consequently altering iron homeostasis. The objective of this study was to determine if abdominal subcutaneous adipose tissue (AbScAT) releases hepcidin in vivo and if release is modified by obesity. Arterio-venous differences in concentrations of hepcidin were measured across AbScAT in 9 obese and 9 lean adults. Overall (n=18), mean plasma hepcidin concentrations were significantly higher in arterialized compared to AbScAT venous samples [mean difference (arterialized-AbScAT venous plasma hepcidin) = 4.9±9.6 ng/mL, P=0.04]. Net regional release was not calculated because mean venous plasma hepcidin concentrations were lower than mean arterialized concentrations indicating no net release. Significant correlations between AbScAT venous and arterialized plasma hepcidin concentrations with anthropometric variables were not observed. Findings from this vein drainage study suggest there is no net release of hepcidin from the AbScAT depot and thereby no ability to signal systemically, even in obesity.